2011
DOI: 10.1111/j.1365-2648.2011.05738.x
|View full text |Cite
|
Sign up to set email alerts
|

Pain and psychological well‐being of older persons living in nursing homes: an exploratory study in planning patient‐centred intervention

Abstract: As the number of older patients increases, so does the need for alternative accommodation; thus, pain management education is urgently needed for staff and nursing home residents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
32
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 38 publications
3
32
1
Order By: Relevance
“…Measuring pain intensity using the FPS-R scale showed that most participants (80%) had moderate to severe pain, which means they assigned the score of 6 or more to their pain severity. Results of a study on elderly adults, from 6 nursing homes in Hong Kong, that used a geriatric pain assessment scale, showed a pain intensity of 4.51 on a 10-point scale, which was lower than our results (17). A recent study of elderly people that resided in the community setting in Brazil showed that 52.8% of the elderly population suffered from chronic pain; among them 54.6% reported highest or the worst possible pain intensity (18).…”
Section: Discussioncontrasting
confidence: 53%
“…Measuring pain intensity using the FPS-R scale showed that most participants (80%) had moderate to severe pain, which means they assigned the score of 6 or more to their pain severity. Results of a study on elderly adults, from 6 nursing homes in Hong Kong, that used a geriatric pain assessment scale, showed a pain intensity of 4.51 on a 10-point scale, which was lower than our results (17). A recent study of elderly people that resided in the community setting in Brazil showed that 52.8% of the elderly population suffered from chronic pain; among them 54.6% reported highest or the worst possible pain intensity (18).…”
Section: Discussioncontrasting
confidence: 53%
“…Previous research has consistently found an association between happiness and subjective well-being among older people (Abe, Fujise, Fukunaga, Nakagawa, & Ikeda, 2012;Adams & Moon, 2009). In particular, a study of 302 older adults in Hong Kong reported higher levels of loneliness, lower levels of life satisfaction, and higher levels of depression when their level of happiness was low (Tse, Leung, & Ho, 2011). Furthermore, the positive association between optimism and subjective well-being, including life satisfaction, purpose in life, and positive affect, as well as the negative association with depressive symptoms has often been found among older adults (Ferguson & Goodwin, 2010;Ferreira & Sherman, 2007;Vahia et al, 2010).…”
mentioning
confidence: 96%
“…Among breast cancer survivors, for example, chronic loneliness is associated with higher levels of pain, depression, and fatigue (Jaremka et al, 2012). Similarly, older adults with chronic pain report being significantly more lonely than do those without pain (Jacobs, Hammerman-Rozenberg, Cohen, & Stessman, 2006; Tse, Leung, & Ho, 2012). Moreover, loneliness predicts more than a four-fold increase in the prevalence of chronic pain among elderly individuals over time (Jacobs et al, 2006).…”
mentioning
confidence: 99%